Stepped care for borderline personality disorder : making treatment brief, effective, and accessible - Paris, Joel, 1940- (Academic Press, 2017)
Synthesizing the latest research and treatment developments, Stepped Care for Borderline Personality Disorder: Making Treatment Brief, Effective, and Accessible aims to make treatment for borderling personality disorder (BPD) more accessible by providing clinicians with innovative brief and targeted intervention methods. Focusing on integrative treatment models, it offers clinicians a vital guide to the management of patients who are difficult to treat. Acknowleding the early developmental roots of BPD, the book includes sections on BPD in adolescence, childhood precursors of the disorder, and a broad range of etiological factors. It looks at the pitfalls clinicians face when trying to treat BPD, and offers a roadmap to avoiding them.